Resiko Pemberian Mgso4 Dosis Awal Full Dose Pasien Preeklamsi Pada Tindakan Persalinan Sectio Caesaria - Azizah, Siti; Sugijati, Sugijati; Palupi, Jenie (Malang Journal of Midwifery (MAJORY), 2019)
Abstract The risk of preeclampsia labor threatens the safety of the mother and fetus. Proper handling is needed to reduce the risk of this incident. Referral preeclampsia patients did not receive full dose of MgSO4 in the treatment at the first health facility. This causes complications to become a severe condition that is accompanied by seizures at any time and increases the risk of maternal or fetal death. The purpose of this study was to determine the risk of giving a full dose of MgSO4 as an initial full dose of preeclampsia patients in caesarean section delivery. The research design is a descriptive study with a cross sectional approach, with a population of 100 mothers of preeclampsia patients who gave birth to Sectio Caesaria and not Sectio Caesaria, sampling using saturated sampling with a total sample of 100 preeclampsia patients who met the inclusion criteria. The research instrument used the patient's medical records, then the data were analyzed using the Chi square test for the one-sided hypothesis and to find out the risk (Odds Ratio) of exposure to the case at a 95% confidence level using a 2x2 table showing the risk of SC in PE patients who were given MgSO4 not full dose is greater than PE patients who are given full dose of MgSO4. Keywords: Full dose Initial MgSO4 Administration, Sectio Caesaria